Understanding consumer's attitude towards online shopping purchase intention / Stephanie Lallai Tuah - Tuah, Stephanie Lallai (Faculty of Business and Management, 2015)
In the era of globalization electronic marketing is a great revolution. The internet as a global medium is quickly gaining internet and attractiveness as the most revolutionary marketing tool. The global nature of communication and shopping has as well redefined, seeing that it is the perfect vehicle for online shopping stores. The large number of Internet users provides a good foundation for the expansion of the online shopping market. Online Shopping is the process of buying goods and services from merchants who sell on the internet,shoppers can visit web stores from the comfort of their homes and shop as they sit in front of the computer. The main purpose of this study is to understanding consumer's attitude towards online shopping purchase intention. The study also investigate how demographic (gender, age, income and education level), factors influencing consumers' attitude towards online shopping and Theory of Reasoned Action (TRA) concept affect consumer's attitude towards online shopping. The findings from this study will allow online businesses to be better informed of what draws consumers or prohibits them from coming their best websites. The better understand awareness of online shoppers, the higher the chance which they can create a center of attention and keep consumers.